MODERN ASPECTS OF PATENT PRACTICE IN THE ACTIVITY OF THE SCIENTIFIC RESEARCH INSTITUTE - A. I. Gromakova; E. V. Korol; O. A. Semkina (Разработка и регистрация лекарственных средств)
The article contains information on the use by scientists of skills and abilities to conduct research in the field of patent science, to introduce the latest and progressive results of your developments into the production process. The presented aspects of the research work of the FGBNU VILAR in the field of intellectual property, allowing to make the results of scientific activity more relevant and significant.